Forensic Aspects of Crime Scene Investigation Using CBRN Agents - Konieczny, Marcin (The Opole Studies in Administration and Law, 2022)
Work entitled Forensic aspects of an incident site investigation using CBRN agents discusses the most important issues related to conducting activities at a specific site where an incident occurred with the use of chemical, radiological and biological agents known as CBRN. The work is divided into four parts - the first discusses the most important aspects of investigating the scene of an incident, the second discusses the research activities carried out at the site of use of CBRN agents, the third presents modern methods of investigating the sites of incidents using these agents, and the fourth provides a general summary. In Poland, conducting forensic activities at the scene of an incident, where CBRN means were used, is based on the one hand on classic methods and techniques of forensics, and on the other hand on the use of special devices for these works. They are undoubtedly a valuable solution and allow for faster and more accurate performance of specific tests.